A context gathering framework for context-aware mobile solutions - Devaraju, Anusuriya; Hoh, Simon; Hartley, Michael (2007)
One of the fundamental design issues in context-aware mobile services development is the necessary support for adequately powerful yet efficient querying of the sensory data. This issue argues for research into the creation of a technology-independent, high-level software application programming interface (API) that provides mechanisms for dealing with the heterogeneity of sensors providing raw context data. In this paper, we review approaches in existing context-aware platforms especially those that consider with sensory data acquisition. The review formed the basis for the design and development of the context gathering framework which consists of sensor data model, messaging and communication protocol and software application programming interface. These components form as one of the enabler to support the development of context aware mobile applications.